Pigs exposed to nitrogen, argon or carbon dioxide filled high-expansion foam: behavioural responses, stun process and blood lactate concentration - C. Lindahl; E. Sindhøj; M.A. Gerritzen; H.G.M. Reimert; C. Berg; M. Blad; A. Wallenbeck (Animal)
According to the EU legislation, all animals farmed for food production must be stunned before being exsanguinated (exempt slaughter prescribed by religious rites). Stunning methods must be reliable, effective, and free from avoidable pain, distress, and suffering, warranting continuous improvement. New methods must be thoroughly evaluated from an animal welfare perspective before approval. One technology developed for on-farm euthanasia and large-scale depopulation for disease control in pigs uses high-expansion foam to create an anoxic atmosphere in a closed container. The method has previously been suggested as a potential method for stunning pigs at slaughter. This study compared the behavioural responses and stun process (e.g., loss of posture and convulsions) of pigs exposed to three different gases (N2, Ar, and CO2) delivered in high-expansion foam. Thirty-six pigs, approximately 12 weeks old, were placed one at a time in a container and exposed to either N2, Ar, or CO2 gas-filled foam for 5 min from foam start. Behavioural observations were conducted from video recordings, assessing time to loss of balance, loss of posture, last strong convulsion and last muscle contraction. Results showed that pigs in the CO2 treatment performed escape attempts significantly earlier than in N2 and Ar, and there were more pigs that performed this behaviour in CO2, indicating that high concentrations of CO2 are more aversive than Ar and N2. Pigs exposed to CO2 foam also avoided the foam earlier compared to the other two gases. Loss of posture occurred earlier in the CO2 treatment, consistent with the anaesthetic effect of CO2. A faster foam filling time for CO2 foam may be a contributing factor to the differences found; however, filling time was adjusted for in the statistical analyses to reduce bias in the comparisons between gases. All pigs across treatments were adequately stunned after 5 min, with no corneal reflex, rhythmic breathing, gagging, or muscle contractions upon removal from the container. No indications of regained consciousness during sticking and bleeding were found. In conclusion, the gas foam method was effective in stunning the pigs regardless of the gas type used. The less aversive responses to Ar and N2 foam are positive from an animal welfare perspective, but the longer time to loss of consciousness compared to CO2 is a disadvantage.